Synthesis of Pt–Ni Alloy Nanocrystals with High‐Index Facets and Enhanced Electrocatalytic Properties1. Issue 46 (4th September 2014) - Xu, Xiling; Zhang, Xin; Sun, Hui; Yang, Ying; Dai, Xiaoping; Gao, Jinsen; Li, Xueyong; Zhang, Pengfang; Wang, Hong‐Hui; Yu, Neng‐Fei; Sun, Shi‐Gang
Abstract The shape‐controlled synthesis of multicomponent metal nanocrystals (NCs) bounded by high‐index facets (HIFs) is of significant importance in the design and synthesis of high‐activity catalysts. We report herein the preparation of Pt–Ni alloy NCs by tuning their shape from concave‐nanocubic (CNC) to nanocubic and hexoctahedral (HOH). Owing to the synergy of the HIFs and the electronic effect of the Pt–Ni alloy, the as‐prepared CNC and HOH Pt–Ni alloy NCs exhibited excellent catalytic properties for the electrooxidation of methanol and formic acid, as well as for the oxygen reduction reaction (ORR).